TREND TINGKAT KESEJAHTERAAN NELAYAN DI WILAYAH PESISIR KABUPATEN KUTAI KARTANEGARA (Trend of Welfare Fishermen at Coastal Area of Kutai Kartanegara Regency) - . Juliani (Bogor Agricultural University, 2012)
The factors affecting the welfare can be classified into economic factors, social, and psychological. One measurement welfare from an economic perspective can done with the exchange rate approach. Value. The exchange must be able to describe the fishery ability of fisheries (catching and aquaculture) to meet the needs of (goods and services) with resources derived from fisheries activities. Measurements with this concept is considered more reflect the actual conditions, because measurements by just looking at the changes income (households) without notice changes in the costs not comprehensively describe their welfare. When the concept of exchange rate fishermen (NTN) and exchange rate farmers fish (NTPi) describes the indicators for measuring the purchasing power of the need goods and services required, then when the value the higher the index of the exchange rate will be more welfare. Location of activities carried out in coastal areas Kutai Kartanegara regency covers Sub District of Muara Badak, Anggana, Sanga-Sanga, Muara Jawa, Samboja, and Marangkayu. The data obtainedin the field (primary) and secondary data is then compiled, categorized and analyzed. The focus of the study consisted of two analytical resultsare Exchange Fishermen (NTN) and Fishermen Exchange RateIndex (INTN) were divided into 3groups: Household Fishermen, fishing by fishing fleet, and fishing based on the type of fishing gear. The exchange rate fisherman (NTN) in total revenues and receipts fishery in 2012 based on their fishing geareach consisting of mini trawl of 1.13 and 1.76; trammel net of 1.16 and 1.69; guiding barrier was 1.04 and 1.94; bottom longline 1.28 and 2.07; crab traps of 1.02 and 1.97; troll line of 1.04 and 1.50; and step on the chart of 1.14 and 1.88. Exchange Rate Index fishermen (INTN) total revenues and receipts fishery in 2012 by fishing geareach consisting of mini trawl of 80.65 and 82.19; trammel net of 74.90 and 72.32; guiding barrier at 68.89 and 68.06; bottom longline at 62.78 and 62.20; crabs traps of 75.01 and 75.17; troll line for 71.64 and 69.18; and step on the chart at 69.29 and 69.76.Key words: fishermen, trend, welfare,